Alumni Engagement and Ordinary-Level Students' Academic Performance in Government-Aided Secondary Schools in Sheema Municipality - Kyorimpa, Adrine; Aheisibwe, Irene; Asiimire, Donah (East African Journal of Education Studies, 2024)
The study aimed to assess Alumni Engagement in ordinary-level students' Academic Performance in Government-aided Secondary Schools in Sheema municipality. The study employed a descriptive research design. The target population was 6 headteachers from 6 secondary schools, 92 teachers, 6 Alumni, Municipal Education Officer (MEO) and Municipal Inspector of Schools (MIS). A sample of 106 respondents was considered for the study from 6 Secondary schools. The study employed interviews and questionnaires as data collection methods. The study considered both qualitative and quantitative methods of data analysis. The study findings revealed that alumni engagement influences the postings and employment of teachers in specialised disciplines, organising training workshops and award ceremonies, developing mentoring avenues, organising inspirational talks, managing student discipline and conducting seminars with students. The study recommendations were the establishment of alumni-sponsored programmes aimed at collaboration with alumni networks to create mentorship programmes, diversification of alumni engagement activities beyond traditional events by leveraging technology, encouraging alumni participation in school improvement projects, such as infrastructure upgrades, and extracurricular activity support, to foster a sense of ownership and investment in the school's development